Long-Lived Plasma Cells in Autoimmunity: Lessons from B-Cell Depleting Therapy - Mahévas, Matthieu; Michel, Marc; Weill, Jean-Claude; Reynaud, Claude-Agnes (Frontiers in Immunology, 2013)
A large number of autoimmune diseases are treated with rituximab, an antibody against CD20 that depletes most of the B cells in the organism. The response to this treatment depends largely on the disease and the type of lymphoid cells involved in the autoimmune process. We recently reported that B-cell depletion in immune thrombocytopenia induced the appearance of pathogenic long-lived plasma cells in the spleen, which were not present before treatment or in non-autoimmune conditions. The spleen of treated patients produced an excess of the cytokine B-cell activating factor (BAFF), which in in vitro-cultured splenic cells, could increase the longevity of plasma cells. Our results suggested that, paradoxically, the B-cell depletion itself, by altering the splenic milieu, promoted the differentiation of short-lived autoimmune plasma cells into long-lived ones. We describe the cellular and cytokinic components of the splenic plasma-cell niche, notably CD4+ T cells and discuss possible survival factors that could be targeted simultaneously with rituximab-mediated B-cell depletion to interfere with plasma-cell persistence.